Role of Supervisor Personality and Procedural Knowledge about Professional Conduct as Predictors of Prosocial Feedback Delivery - Ock, Jisoo (Korean Journal of Industrial and Organizational Psychology, 2023)
Implicit trait policy (ITP) theory argues that the relationship between personality and behavior is mediated by implicit trait policy, or effectiveness beliefs that people hold about trait-expressive behaviors in social situations. Also, ITP theory argues that personality affects ITPs, such that people are likely to hold stronger effectiveness beliefs about behaviors that express their own personality than behaviors that do not. The current study applied the ITP theory perspectives explained above in the context of feedback delivery in organizational settings to test the hypothesis that supervisor agreeableness is related to prosocial feedback (e.g., showing empathy and kindness in providing performance feedback) through its relationship with effectiveness beliefs about prosocial behavior at work (i.e., prosocial ITP). Based on the data that were collected from a sample of supervisors (N = 248), we found that supervisor agreeableness was related to prosocial feedback delivery only through its relationship with prosocial ITP.